Pengaruh Gaya Mengajar Tutor terhadap Minat Mahasiswa Menggunakan Aplikasi MYOB Accounting dengan Gender sebagai Pemoderasi - Liana Dewi (Fakultas Vokasi Universitas Mayasari Bakti, 2023)
Mastery of technology in accounting is something that needs to be considered in this era. Educational institutions are challenged to be able to produce graduates who have good mastery in accounting and use technology to increase effectiveness and efficiency in their work. To meet these challenges, educational institutions provide lectures related to the management of financial data using accounting software, one of which is MYOB accounting. This study aims to examine the influence of the tutor's teaching style on students' interest in learning MYOB accounting moderated by gender. This research is a quantitative research. The sample used in this study were students of the accounting study program for Islamic financial institutions at the Mayasari Bakti University campus who had obtained the financial accounting practicum course 2. Data was collected through a questionnaire. The results of the study stated that the tutor's teaching style had a significant effect on students' interest in studying MYOB accounting. Meanwhile, gender is not able to moderate the relationship between the tutor's teaching style and students' interest in studying MYOB accounting. Keywords: MYOB accounting, tutors, student interests, gender.